The role of informal learning in adults’ literacy proficiency - Sari Sulkunen; Kari Nissinen; Antero Malin (European Journal for Research on the Education and Learning of Adults)
This study used the PIAAC dataset to compare the effects of informal literacy learning on adults’ literacy proficiency to those of formal and non-formal learning. The study participants were Nordic adults aged 35–65 years. The statistical method was regression analysis. The results indicate that informal literacy learning had the most significant effect on Nordic adults’ literacy proficiency. Non-formal adult education had a clearly smaller effect, and formal adult education seemed to have a negative effect when background factors were controlled for. Informal learning, particularly reading outside work, had a significant effect independent of adults’ backgrounds, indicating that it offers also less-educated and unemployed adults the opportunity to develop literacy proficiency.